Progress in Biomedical Applications of Tetrahedral Framework Nucleic Acid-Based Functional Systems - Zhang, Tao; Cui, Weitong; Tian, Taoran; Shi, Sirong; Lin, Yunfeng (ACS applied materials & interfaces, 2020)
The past decades have witnessed the development of DNA nanotechnology and the emergence of various spatial DNA nanostructures, from two-dimensions to three-dimensions. The typical example is the tetrahedral framework nucleic acid (tFNA). In this review, we summarize the progress in fabrication, modification of tFNA-based functional systems and their potentials in biomedical applications. Through a one-step assembly process, tFNA is synthesized via four single stranded DNAs with three short sequences complementary to the other sequence of another single strand. Characterizations including polyacrylamide gel electrophoresis, atomic force microscopy, and dynamic light scattering measurement show tFNA as a pyramid-like nanostructure with the size of around 10 nm. Feathered with intrinsic biocompatibility and satisfactory cellular membrane permeability, the first generation of tFNA shows promising capacities in regulating cell biological behavior, promoting tissue regeneration, and immunomodulation. Along with excellent editability and relative biostability in complicated conditions, tFNA could be modified via hanging functional domains on the vertex or side arm and incorporating small-molecular-weight drugs to form the second generation, for reversing multidrug resistance in tumor cells or microorganisms, target therapy, anticancer and antibacterial treatments. The third generation of tFNA is currently tried via a multistep assembly process for stimuli-response and precise drug release. Although tFNAs show promising potentials in cargo delivery, massive efforts still need to be made to improve biostability, maximal load, and structural controllability.